Different Attitudes Towards the Assessment of Learning Results - Šventickas, Algimantas (Acta Paedagogica Vilnensia, 2002)
Classical didactics paid a special attention to a mark as the estimation of student’s progress. It is possible to notice some remained mark fetishism, especially in education practise. In comparison with testing teaching results, assessment nation and broader (expresses the relation between what the student knows and what he has to know at the moment of assessment), and at the same time narrower (express the subjective attitude of the teacher) but this is not the only expression. Mark is interpreted as a measure of completeness and quality of learning results. Mark – is the index of an educational activity, reflecting students’ knowledge, skills showing if a student fulfilled the task properly, if he was active. Mark is the characteristic of an educational and cognitive activity. It educates influences the students’ consciousness and feelings, therefore students themselves and their parents are much worried about getting better assessment. It is growing clear, that students have developed the need of being assessed, if their knowledge and work are regularly tested and assessed by a teacher, they have realised that testing and assessment help to study better and more responsible. Thus marks hinder and help to humanise teaching and learning. If students understand the assessment of knowledge as threat and despotism, they can study more for marks, but no for gaining knowledge. A teacher has to be attentive to his marking system and assessment methods, shouldn’t stimulate students to study under compulsion, which they wouldn’t learn. Improper methods of testing and assessment can discourage students to do what is required. Paying attention to that teachers and psychologists are continually discussing how to improve assessment by marks and how to present them. Obviously that information about a student should be useful. Marks are considered to be very important in our society, therefore teachers should be very careful about giving marks. In case of hesitation the assessment should be done in favour of a student. Because the system of assessment is not perfect and you should pay attention to the psychological. And social conditions. After analysing the results it became clear that 81% of teachers think that their students’ assessment is objective, however still 45% of students support this kind of teachers’ opinion (p < 0.001). Only 37% of the students and 14% (p < 0.00 l) of the teachers consider that only a small part of teachers are objective in assessment. That is why the greater part of the teachers is assured that they assess the learning results objectively, though more than half of the students (52%) think contrarily. Students say: "most teacher are objective but not always", "students themselves are the best judges of their knowledge". Different teachers understand the statement "most teachers are objective assessing the learning results" differently. 50% of the teacher - experts consider so, 72% of the teachers - methodologists, 81 % of the senior teachers as well as 90% of the teachers. The rest 50% of the teachers - experts think that rather a few teachers assess students’ knowledge objectively and 22% of the teachers - methodologists, 13% of the senior - teachers and 9% of the teachers do agree with them. According to the data it can be affirmed that the higher teachers’ pedagogical qualification the more they hesitate in other teachers’ objectivity.